Implementation of a Character-Based Islamic Religious Education Learning Model in Improving the Morality of Students at Al Mudhofar Islamic Elementary School - Amaliyah, Amaliyah; Futaqi, Sauqi; Rahmawati, Zuli Dwi (Yayasan Rahmat Islamiyah, 2025)
This study aims to describe the implementation of a character-based Islamic Religious Education (PAI) learning model in improving student morality at Al Mudhofar Islamic Elementary School. The method used in this study is a qualitative research method using a case study technique to explore learning strategies, teacher roles, habituation activities, as well as supporting and inhibiting factors in the implementation of this model. The results of the study indicate that the integration of character values into PAI learning through a contextual approach, teacher role models, and daily habituation activities such as congregational prayer, moral journals, and the Friday blessing program has a positive impact on the formation of honesty, discipline, and responsibility in students. The success of this implementation is supported by an Islamic school culture, the visionary leadership of the principal, and the active involvement of parents.